Pengaruh Inklusi Keuangan Dan Literasi Keuangan Terhadap Kinerja Keuangan Pada BSI Region Medan - Yusti Laila; Mutiah Khaira Sihotang (Al-Sharf: Jurnal Ekonomi Islam, 2022)
This study aims to determine the effect of financial inclusion and financial literacy on financial performance in the region medan BSI. The data collection technique in this study used a questionnaire, which is in the from of a data collection technique which is carried out by providing questions and written statements to respondents to be answered. The population in this study was all employees in the BSI medan Region. The sample was taken using a saturated sampling technique (total sampling) with a total of 17 employees. The data analysis techniques used in this study are Validity Test, Reliability Test, Normality Test, Multicholinearity Test, Heteroskedasticity Test, t Test, f Test, r Test, Multiple Linear Regression using the help of SPSS. The obtained multiple linear equation Y= 5.327 + 0.444 + 0.438. The results showed that there was an influence of financial inclusion on financial performance with a value of sig = 0.041 and t_hitung 2.256 > t_tabel 2,131, there was an effect of financial literacy on financial performance with a value of sig = 0.026 and t_hitung 2,486 > t_tabel 2,131, simultaneously there is an influence of financial inclusion and financial literacy on financial performance with a value of sig = 0.002 and a calculation of 9.549. The value of R Square of 57.7% the remaining 42.3% is influenced by other variables that are not studied. The conclusion of the financial inclusion research affects financial performance, financial literacy affects finances, simultaneously financial inclusion and financial literacy affect financial performance in BSI Medan Region.